2014
DOI: 10.1007/s00210-014-1019-8
|View full text |Cite
|
Sign up to set email alerts
|

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency

Abstract: Arsenic trioxide (As2O3) is used to treat acute promyelocytic leukemia. However, the cardiotoxicity of long QT syndrome restricts its clinical application. Previous studies showed that As2O3 can damage the human ether-a-go-go-related gene (hERG) current via disturbing its trafficking to cellular membrane. This study aimed to investigate whether the As2O3-insulted hERG channel can be rescued by resveratrol, a recognized cardioprotective agent. The whole-cell patch clamp technique was used to record the hERG cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…We first chose the cardioprotective drug, resveratrol, which was used to correct trafficking defect caused by arsenic trioxide via acceleration of interaction between hERG and chaperones, and alleviation of ER stress. 14 In addition, resveratrol shortened APD 50 and APD 90 recorded in freshly isolated guinea pig ventricular myocytes by inhibition of I ca-L and restoration of I kr when co-incubated with arsenic trioxide. We also used astemizole (an antihistamine drug), a high-affinity blocker of hERG channel, which is thought to interact with the amino acid residue Tyr652.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We first chose the cardioprotective drug, resveratrol, which was used to correct trafficking defect caused by arsenic trioxide via acceleration of interaction between hERG and chaperones, and alleviation of ER stress. 14 In addition, resveratrol shortened APD 50 and APD 90 recorded in freshly isolated guinea pig ventricular myocytes by inhibition of I ca-L and restoration of I kr when co-incubated with arsenic trioxide. We also used astemizole (an antihistamine drug), a high-affinity blocker of hERG channel, which is thought to interact with the amino acid residue Tyr652.…”
Section: Discussionmentioning
confidence: 93%
“…Resveratrol is able to rescue the trafficking inhibition of hERG and relieve the ER stress triggered by arsenic trioxide. 14 Astemizole promotes forward trafficking from ER to cell surface inhibited by pentamidine in a competitive way. 5 Fexofenadine is often used to rescue trafficking defect of hERG because of the advantage that rescue without blocking the channel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicated that As 2 O 3 -induced hERG-channel abnormality was probably due to other reasons, like trafficking deficiency. 10 …”
Section: Resultsmentioning
confidence: 99%
“… 8 Also, probucol and As 2 O 3 are the two main kinds of drugs to decrease hERG expression and subsequently cause LQTS. 9 , 10 Therefore, we wondered whether these two drugs, which can induce hERG-channel deficiency, were involved in the ubiquitination protein-degradation pathway. Based on this, we became interested in SGK1 expression after treatment with different concentrations of probucol or As 2 O 3 in hERG-HEK293 cells.…”
Section: Introductionmentioning
confidence: 99%